Individual Assistance Programs from FEMA - Carol Fountain; Michael T. Olexa; Jana Caracciolo; Lauren Grant (EDIS)
Individuals, families, and businesses may be eligible for federal assistance from the Federal Emergency Management Agency (FEMA). You are eligible if you live, own a business, or work in a county declared a Major Disaster Area; incur sufficient property damage or loss; and do not have the insurance or other resources to meet your needs. This 3-page fact sheet is a minor revision written by Michael T. Olexa, Jana Caracciolo, and Lauren Grant, and published by the Food and Resource Economics Department, October 2019.